DEVELOPMENT STRATEGY OF OIL PALM FARMERS'REVENUE - Saifuddin, Saifuddin; Suadi, Suadi; Suryadi, Suryadi; Fadli, Fadli (Jurnal Aplikasi Manajemen, 2017)
This study aims to explain the impact of oil palm-cattle integration to increase the revenue of oil palm farmers Community in East Aceh. The method used in this study was descriptive qualitative. The data has been analyzed through three stages, the first stage is data reduction, the second stage is data display and the last stage is the conclusion. The results showed that the integration of oil palm with cattle have a positive impact on increased farmers'revenue in East Aceh, it estimated approximately at 60% to 80%. This depends on the integration model being implemented, whether by letting the cattle graze freely (wild-release system) or by grazing them safely (enclosure system) and put the cattle in the cage at night.